Type I IFNs Are Required to Promote Central Nervous System Immune Surveillance through the Recruitment of Inflammatory Monocytes upon Systemic Inflammation - Peralta Ramos, Javier María; Bussi, Claudio; Gaviglio, Emilia Andrea; Arroyo, Daniela Soledad; Baez, Natalia Soledad; Rodriguez-Galan, Maria Cecilia; Iribarren, Pablo (Frontiers in Immunology, 2017)
Brain-resident microglia and peripheral migratory leukocytes play essential roles in shaping the immune response in the central nervous system. These cells activate and migrate in response to chemokines produced during active immune responses and may contribute to the progression of neuroinflammation. Herein, we addressed the participation of type I-II interferons in the response displayed by microglia and inflammatory monocytes to comprehend the contribution of these cytokines in the establishment and development of a neuroinflammatory process. Following systemic LPS challenge, we found glial reactivity and an active recruitment of CD45hi leukocytes close to CD31+ vascular endothelial cells in circumventricular organs. Isolated CD11b+ CD45hi Ly6Chi Ly6G- primed inflammatory monocytes were able to induce T cell proliferation, unlike CD11b+ CD45lo microglia. Moreover, ex vivo re-stimulation with LPS exhibited an enhancement of T cell proliferative response promoted by inflammatory monocytes. These myeloid cells also proved to be recruited in a type I interferon-dependent fashion as opposed to neutrophils, unveiling a role of these cytokines in their trafficking. Together, our results compares the phenotypic and functional features between tissue-resident versus peripheral recruited cells in an inflamed microenvironment, identifying inflammatory monocytes as key sentinels in a LPS-induced murine model of neuroinflammation.